A Study To Assess Knowledge Regarding Zika Virus Among The Community People In Selected Areas Of Pune City (International Journal of Food and Nutritional Sciences, 2022)
The majority of people infected with Zika virus exhibit no symptoms or signs of infection. Certain individuals experience a little increase in warmth, redness, and muscular soreness. Even in persons who exhibit no signs or symptoms of infection, the Zika virus may cause brains or central nervous diseases such as Guillain-Barre syndrome.Objective: To assess the knowledge regarding Zika virus among the community people and assess the association score between knowledge and selected demo-graphical variables.Materials and Methods: The study adopted Non-Experimental Descriptive design carried out among200 people.Non-probability purposive sampling technique was used and was statically analysed after collecting the data through structured questionnaire was prepared for data collection . Self Structured questionnaires regarding knowledge on Zika virus used for the data collection . Ethical clearance was taken from the Institutional ethics committee. Data analysis was done using descriptive statistics.Results: The present study result showed that Knowledge concerning Zika virus among the community people Majority 59% were having average knowledge, 24.5% were having good knowledge, 15% were having poor knowledge and 1.5% were having excellent knowledge.